A Study of Consumer Behavioral Intentions of Online Purchases - Bryan Mung Kit Ng; Zhen Cai; Sheng Jie Cao; Ze Lei Cao; Alya Zikrina Rabba; Gan Kia Hui; Kok Ban Teoh (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
This study explores the impact of service quality, product quality, product freshness, and time savings on consumer behavioral intentions in online shopping, particularly in the post-COVID-19 era. With the rapid growth of e-commerce, understanding factors that influence consumer behavior is critical for businesses seeking to enhance customer loyalty. The primary objective is to identify which factors significantly affect online purchasing intentions. Using both primary and secondary data, a digital questionnaire was administered to 160 respondents. The collected data were analyzed using multiple regression analysis through IBM SPSS Statistics software to test four hypotheses. The results show that service quality (? = 0.472, p 0.001), product quality (? = 0.217, p = 0.001), and product freshness (? = 0.212, p = 0.002) are significant predictors of behavioral intention, while time savings (? = 0.086, p = 0.320) is not. These findings highlight the importance of focusing on quality and freshness in the online marketplace. Businesses should prioritize these factors to improve customer satisfaction and loyalty. The study concludes that while time savings are often valued in online shopping, it does not significantly drive consumer intentions, making service and product excellence more critical for success in the evolving digital economy.